2010
DOI: 10.22452/jummec.vol13no2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Acupuncture in Saudi Arabia

Abstract: Acupuncture is one of the oldest and most commonly used complementary medical procedures in the World. Although it is not free from side effects, its use is becoming increasingly popular. The aims of this study were to describe the demographic characteristics of acupuncture users in Riyadh, Saudi Arabia and their knowledge, attitude and experience regarding acupuncture, as well as to determine the common complaints for which patients seek help from acupuncture centers. A cross sectional study, which targeted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In Saudi Arabia, the prevalence of dealing with CM was found to be 68%. Some studies suggest that many people used the CM after they were advised by their relatives or friends [5,6]. A study was conducted in Riyadh about the use of CM in adults with neurological diseases which revealed that cupping was the most utilized method (45.4%) followed by herbs (42.3%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the prevalence of dealing with CM was found to be 68%. Some studies suggest that many people used the CM after they were advised by their relatives or friends [5,6]. A study was conducted in Riyadh about the use of CM in adults with neurological diseases which revealed that cupping was the most utilized method (45.4%) followed by herbs (42.3%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of late, the current practices like acupuncture were also launched in the Saudi community by entrenched private clinics (AlBedah et al, 2011;Sayed et al, 2014). Contradictory to Saudi Arabia, the frequently used CAM practices in the Western world (MO, 2010;Mansour et al, 2015) are relaxation technique, (MacLennan et al, 1996) chiropractic, massage and homeopathy (Eisenberg et al, 1993;Goldbeck-Wood et al, 1996) . The mistrust of some patients for conventional medicine, belief it has more side-effects and dissatisfaction with previously used conventional medicine that they had used previously had made them shift to CAM (Jaiswal et al, 2015;El-Gendy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%